Pengaruh Penggunaan Fintech, Tingkat Keterampilan Teknologi, dan Peran Media Sosial, Terhadap Literasi Keuangan Mahasiswa Jurusan Manajemen di Universitas Teuku Umar - Cut Sartika (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to determine the effect of fintech usage, the level of technological skills, and the role of social media on the financial literacy of management students at Universitas Teuku Umar. The background of this research is based on the phenomenon of the increasing use of digital financial services among students, which has not been accompanied by an adequate improvement in financial understanding. This research is quantitative in nature with an associative approach, in which the data were obtained through the distribution of questionnaires to 86 management students at Universitas Teuku Umar. The data analysis techniques used include descriptive analysis, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, as well as t-tests and F-tests to examine the research hypotheses. The results show that the fintech usage variable does not have a significant effect on students’ financial literacy, with a t-value of 0.132, a beta coefficient (β) of 0.014, and a significance value of p = 0.895 > 0.10. This indicates that students tend to use fintech services only for transactional purposes, such as payments and fund transfers, rather than to improve their financial understanding and financial management skills. In contrast, the level of technological skills has a significant effect on financial literacy, with a t-value of 3.411 and a significance value of 0.001 < 0.10. Likewise, the role of social media has a significant effect on students’ financial literacy, with a t-value of 3.379 and a significance value of 0.001 < 0.10. Meanwhile, the results of the simultaneous test (F-test) show that the three independent variables jointly have a significant effect on financial literacy, with an F-value of 48.826 and a significance value of 0.000 < 0.10. From these results, it can be concluded that the level of technological skills and the role of social media have a real influence on improving students’ financial literacy, while fintech usage has not yet had a significant impact. Therefore, improving financial literacy needs to be accompanied by digital education and the wise use of social media as a means of financial learning.